(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Two field experiments were conducted at Bangladesh Agricultural University campus and Gonsar Mor, Mashkanda, Mymensingh during January to May 2018 to evaluate the nutrients and heavy metal contents in soil and crop. Freshwater and wastewater irrigation and four varieties of rice: V1 (BINA dhan11), V2 (BRRI dhan28), V3 (BRRI dhan29) and V4 (BRRI dhan58) were used with three replications. Analyses of wastewater for pH, EC, DO and heavy metals (Pb, Ni, Cd and Cr), soil (before land preparation and after harvest) for pH, EC, OM, N, P, K and heavy metals (Pb, Ni, Cd, Cr), straw and grain for N, P, K and heavy metals were done using standard methods. The pH, EC, Pb, Ni, Cd and Cr content of wastewater was 7.4, 0.612 mS cm-1, 4.3 ppm, 0.09 ppm, 0.40 ppm and 1.80 ppm, respectively. The values of pH, EC, Pb and Ni were within the permissible limit whereas Cd and Cr content in wastewater exceeded the permissible limit for irrigation. OM, N, P and K contents were higher in wastewater irrigated soil and average Cd (0.014 ppm) and Cr (44.81 ppm) content of soil under wastewater irrigation was within the permissible limit. Nutrients and heavy metals (Cd: 0.001 to 0.006 ppm; Cr: 0.49 to 0.59 ppm) contents of straw and grain were also higher under wastewater irrigation. Bioaccumulation and translocation factors for Cd ranged from 0.103 to 0.431 and 0.097 to 0.865 and for Cr ranged from 0.011 to 0.013 and 0.010 to 0.012, respectively. Significant variations were found among four varieties regarding nutrient contents of straw as well as bioaccumulation and translocation of Cd in grain. Bioaccumulation factor was <1, indicating absorption only, not accumulation of Cd and Cr in straw or grain, and municipal wastewater can safely be used as an alternate water source for irrigation. J Bangladesh Agril Univ 18(1): 47–54, 2020 https://doi.org/10.5455/JBAU.76696